Associations of academic environment, lifestyle, sense of coherence and social support with self-reported mental health status among dental students at a university in Brazil: a cross-sectional study - Mario Vianna Vettore; Andréa Neiva da Silva (BMJ Open)
Objectives The study evaluated the association of academic environment, lifestyle, sense of coherence (SOC) and social support with self-reported mental health status among dental students.Design Secondary analysis of data from a cross-sectional, questionnaire-based survey conducted from August to October 2018.Setting Dental school of a public-funded university in the south-eastern region of Brazil.Participants 233 undergraduate dental students recruited across all years of the course.Outcome measures Socioeconomic and demographic characteristics, city of origin and student’s academic semester were obtained through self-completed questionnaires. Perception of the academic environment (Dundee Ready Education Environment Measure (DREEM)), individual lifestyle (Individual Lifestyle Profile Questionnaire (ILPQ)), SOC (SOC Scale (SOC-13)), social support (Medical Outcomes Study Scale (MOS)), and depression, anxiety and stress (Depression, Anxiety and Stress Scale-21 (DASS-21)) were assessed using validated instruments. The relationships between variables were investigated through multivariable negative binomial regression to obtain the rate ratios (RRs) and 95% CIs.Results Female sex was associated with greater scores of anxiety (RR 1.74, 95% CI 1.10 to 1.97) and stress (RR 1.52, 95% CI 1.12 to 2.06). Students who perceived a better academic environment and those reporting a greater SOC had a lower probability of depression, anxiety and stress. Furthermore, a favourable lifestyle was associated with lower depression scores (RR 0.99, 95% CI 0.97 to 0.99). Social support did not remain associated with depression, anxiety and stress after adjustment.Conclusions The present findings suggest that self-reported mental health status is associated with students’ sex, academic environment, SOC and lifestyle. Enhancing the educational environment and SOC, and promoting a healthy lifestyle may improve the psychological health of dental students.